Will the urban agricultural revolution be vertical and soilless? A case study of controlled environment agriculture in New York City. (April 2019) - Goodman, Wylie; Minner, Jennifer
Abstract: Controlled environment agriculture (CEA) is an emerging form of farming increasingly found in cities worldwide. Advocates promote CEA as the future of food production, arguing for its potential to address challenges ranging from climate change to food insecurity. Detractors state that CEA's narrow focus on high-end produce, along with its intensive capital and energy needs, limit its meaningful contribution to the urban food system. Over the last seven years, New York City has become an epicenter for urban CEA, offering planners an in-situ setting in which to evaluate its impact. The following case study examines the current state of CEA in New York City, its composition, requirements, and future. The authors identify CEA's relative contributions, which include providing a small number of green-sector jobs and increasing access to produce in low-income communities. In parallel, they question if CEA provides sufficient benefits to warrant public-sector support. Recommendations for cities considering CEA include critically analyzing its purported benefits; evaluating the environmental, economic and social potential of projects located on publicly-owned rooftops and land; and focusing incentives on nonprofit and institutional production that show clear community benefits.